Pengaruh Mobilisasi Progresif Terhadap Kejadian Dekubitus Pada Pasien Dengan Ventilasi Mekanik Di Ruang ICU RSD Mangusada - Padmiasih, Ni Wayan (Universitas Muhammadiyah Surabaya, 2020)
ICU patients who are fitted with breathing equipped, especially mechanical ventilation, tend to have limited activity or immobilization. Long-term immobilization is a high risk factor that causes pressure ulcer. Appropriate prevention is needed because pressure ulcer has a detrimental impact on body functions and quality of life. This study aimed at identifying the effect of progressive mobilization on pressure ulcer incident in patient with mechanical ventilation in Intensive Care Unit at Mangusada Hospital.Design of this study was Pre Experiment (one group pretest and posttest design) with the number of sample was 6 respondents which was chosen through Purposive Sampling technique. Instrument used in this study was a standard procedure of Richmond Agitation Sedation Scale (RASS) and observation sheet of Decubitus.The result of the test indicated most of respondent experience grade I pressure ulcer (decubitus) before being given progressive mobilization therapy and after the therapy, all respondents (100%) did not showed pressure ulcer (decubitus) incident. Wilcoxon test showed that there was an effect of progressive mobilization on pressure ulcer incident in patient with mechanical ventilation in Intensive Care Unit at Mangusada Hospital (p-value = 0,042). Based on the results of this study, it is expected that this study can be used as an evidence based practice nursing, especially about pressure ulcer.